Comparing the self‐perceived effects of a facial anti‐aging product to those automatically detected from selfie images of Chinese women of different ages and cities. Issue 5 (6th April 2021) - Flament, Frederic; Maudet, Aurelie; Ye, Chengda; Zhang, Yuze; Jiang, Ruowei; Dubosc, Sarah; Even, Maxime; Tournery, Sylvia; Abric, Aurelie; De Boni, Maxime; Delaunay, Caroline; Aarabi, Parham
Abstract: Objective: To assess the agreement, after 1‐month application of a popular and efficient anti‐aging product, between self‐perceived facial signs of aging and those detected and graded by an automatic A.I‐based system, using smartphones' selfie images. Material and Methods: Of 1065 Chinese women, aged 18‐60 years, from eight different Chinese cities were recruited. They were asked to apply daily, for 1 month, a referential anti‐aging product onto their whole face. Selfie images were taken by all subjects at D0 and D28 and sent to our facilities for being analyzed through 10 different facial signs. At D28, all subjects were asked to fill a questionnaire on the status of their faces, through six general statements. Results: A global agreement between both approaches is reached, particularly among women older than 40 years where the severity of facial signs is already more pronounced or among younger women who present at least facial signs scored above one grading units. This limit becomes, therefore, a prerequisite in the recruitment of Chinese subjects in the case of anti‐aging applied studies and possible automatically based on automatic grading system. When respecting such conditions, the positive effects of the product on most facial signs can be demonstrated after 28 days of successive applications. Conclusion: Such methodological approach paves the road in fulfilling the need of consumers of a better transparency in the claims of an anti‐aging product.